Preservation of farmed carp (Naini) fish by salting followed by drying and it's quality evaluation - Basnet, Dharma Raj; Bhattarai, Rewati Raman; Mishra, Achyut; Rai, Basanta Kumar (2013)
Salting and drying of fish was studied for preservation of Naini fish. Quality evaluation was done to study the shelf life. Naini fish was procured from Regional Agricultural Rearch station, Tarahara, Sunsari, Nepal. Three different treatment temperature (RT, 4°C and 10°C), different brine of salt concentration (4%, 8%, 12% and 16%) and four different brine treatment times (6, 12, 18, 24 hours) were optimized in this study. Sensorically, at RT (26°C) in brine of 12% salt concentration for 12 hours, at 4°C in brine of 16% salt concentration for 24 hours and at 10°C in brine of 16% salt concentration for 18 hours were optimized for Naini fish preservation. Peroxide values of these three best samples were evaluated for quality (shelf life) upto three months at 1.5 months interval. At the end of present study, peroxide value of all three samples were within acceptable limit (PV<8 meq O2/kg). Peroxide value of sample treated at10°C in brine 16% salt concentration for 18 hours was found to be significantly least (5.46 meq O2/kg). Thus for preservation and longer shelf life, treatment of Naini fish at 10°C in brine of 16% salt concentration for 18 hours and drying thereafter to about 8% moisture is the best condition.